Challenges of opening Islamic windows in traditional banks –The case of Algeria - - Lalaa Ramdani; Ou Elkhair Elbaroud (Journal of Excellence for Economics and Management Research, 2017)
The success of Islamic banks around the world, especially in light of the recent global financial crisis, has prompted conventional banks to adopt the Islamic banking model as a strategic alternative to financing alternatives by mobilizing savings and mobilizing individuals and institutions.   In view of the many forms of work in the Islamic financial industry, traditional banks have opened Islamic windows or windows in the form of an administrative unit within the organizational structure of these banks to attract more available financing resources and diversify the services offered.   Therefore, in this study we will analyze the reality and challenges of establishing Islamic windows in Algeria